No particularly negative impact of the Covid-19 pandemic on the mental health of individuals with higher levels of childhood trauma - Weiss, Elisabeth M.; Fink, Andreas; Papousek, Ilona; Exenberger-Vanham, Silvia; Lampe, Astrid; Dresen, Verena; Canazei, Markus (Frontiers in Psychiatry, 2025)
BackgroundInitial studies suggest that individuals with a history of traumatic life experiences, particularly childhood trauma, may be more susceptible to increased mental health problems in the wake of the COVID-19 pandemic.MethodsThe present cross-sectional study compared the mental health status of three cohorts of university students before (2016), at the beginning (2020) and at the end (2022) of the COVID-19 pandemic. The students in each cohort were divided into two groups: those with self-reported moderate/severe childhood trauma (n = 126) and those with no/mild childhood trauma (n = 438).ResultsAcross all cohorts, students with moderate/severe childhood trauma consistently reported higher levels of psychological and physical stress compared to individuals with no/mild childhood trauma experiences. However, only the no/mild childhood trauma group exhibited an increase in mental health problems (i.e., heightened depressive symptoms and greater subjective impairment due to physical and psychological symptoms) during the COVID-19 pandemic. Furthermore, within the no/mild childhood trauma group, students in the 2022 cohort reported significantly higher psychological distress compared to those surveyed in 2020. In contrast, mental health scores among students with moderate/severe childhood trauma remained unchanged across the pre-pandemic and pandemic cohorts.ConclusionsThe findings of this study do not support the hypothesis that the COVID-19 pandemic disproportionately exacerbated mental health problems in individuals with a history of moderate to severe childhood trauma. Instead, our results suggest that the pandemic’s impact on mental health was more pronounced in students with no or only mild childhood trauma.